Mixed Feelings - Budzyna-Dawidowski, Mateusz (Auckland University of Technology, 2022)
This thesis consists of practice-led research in the form of a full-length script for a feature film [or pilot for television, or play for the theatre]; plus a 6000-word essay (exegesis). A summary of the script is as follows: Anya and Marcel are a young couple starting work together at a company with a highly developed virtual workspace. They develop avatars there: Emma/Anya, who is trained by Jennifer to suppress her own emotions to harvest the emotional data of others, and Francis/Marcel, who is trained by Roy to have his emotional data harvested. Marcel and Anya’s home relationship is tarnished because of Marcel’s growing avoidant nature. Anya cheats on Marcel, and when she sees that Marcel is indifferent, she leaves him. Despite Emma/Anya confessing her cheating, her and Francis/Marcel’s relationship in Enigma flourishes. Momentarily suppressing her love, Emma/Anya helps Jennifer harvest Francis/Marcel’s emotions. Francis/Marcel is left with no emotional memory of who Emma/Anya is to him. Months later, Emma/Anya is frustrated at having to see Francis/Marcel being harvested repeatedly. Unintentionally provoked by Roy at Enigma, Emma/Anya explodes in an emotional meltdown. Her emotions are harvested. After the harvesting, Francis/Marcel and Emma/Anya cannot recognise each other emotionally. They use a virtual space to imagine their old apartment, and they realize who they are to each other and agree to give each other an opportunity to love again. The script is framed by an Exegesis which is a 6000-word essay on the subject of: (a) the genre of the script (b) the development process from synopsis to second draft